Editors' Choice—Washing of Nickel-Rich Cathode Materials for Lithium-Ion Batteries: Towards a Mechanistic Understanding. Issue 16 (3rd December 2019) - Pritzl, Daniel; Teufl, Tobias; Freiberg, Anna T. S.; Strehle, Benjamin; Sicklinger, Johannes; Sommer, Heino; Hartmann, Pascal; Gasteiger, Hubert A.
Abstract : Washing is a commonly used method to remove surface impurities of cathode materials for lithium-ion batteries. However, a clear mechanistic understanding of the washing process is missing in the literature. In this study, we will investigate the effect of washing and subsequent drying of nickel-rich NCM cathodes (85% nickel) with respect to gassing and impedance of the washed cathodes. By on-line electrochemical mass spectrometry (OEMS), we will show a drastic reduction of the O2 release above 80% SOC for the NCM washed with deionized water, suggesting the formation of an oxygen-depleted surface layer on the NCM particle surface. The modification of the surface can be confirmed by a strong impedance buildup of cathodes composed of washed NCM (using a micro-reference electrode in a full-cell), revealing that the impedance increases strongly with increasing drying temperature after washing. Last, we will propose a comprehensive mechanism on the processes occurring during the washing/drying process of nickel-rich NCM materials and identify the drying temperature after washing as the dominant factor influencing the surface properties.